Analysis of Fatty Acid Profile, α-Tocopherol, Squalene and Cholesterol Content in Edible Parts and By-Products of South Pacific Wild Fishes - Sussi López-Puebla; María Fernanda Arias-Santé; Jaime Romero; Adriano Costa de Camargo; Miguel Ángel Rincón-Cervera (Marine Drugs)
Fish are generally rich sources of n-3 polyunsaturated fatty acids such as EPA and DHA, and although the edible part (fillet) has been analyzed in many species, less is known about the composition of fish by-products. The analysis of these materials allows them to be evaluated as raw sources of EPA and DHA, thus contributing to sustainable practices to produce healthy oils for human consumption. This work provides information on the fatty acid profiles, lipid quality indices and α-tocopherol, squalene and cholesterol contents in fillets, heads, bones and viscera of three fish species (anchovy, chub mackerel and Chilean jack mackerel). Samples were lyophilized and lipids were extracted using either the Folch or Hara and Radin methods. FA profiles were obtained by gas chromatography coupled with flame ionization detection, and tocopherol, squalene and cholesterol analyses were performed by high performance liquid chromatography with UV-visible detection. The highest levels of EPA were found in anchovy fillet (18.9–20.6%) and bone (14.7%), while DHA was more abundant in anchovy fillet (16.9–22.0%) and Chilean jack mackerel fillet (15.4–16.6%) and bone (13.1–13.8%). α-Tocopherol, squalene and cholesterol contents ranged from 0.18 to 1.35 mg/100 g, 0.07 to 0.80 mg/100 g and 30.46 to 246.17 mg/100 g, respectively, in the different tissues analyzed from the three fish species.